Nanoengineered Red Blood Cells Loaded with TMPRSS2 and Cathepsin L Inhibitors Block SARS-CoV-2 Pseudovirus Entry into Lung ACE2+ Cells - Yang, Hui (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.